Constitutive Immune Activity Promotes Tumorigenesis in Drosophila Intestinal Progenitor Cells. - Petkau, K.; Ferguson, M.; Guntermann, S.; Foley, E. (Cell reports, 2017)
Gut innate immune defenses control bacterial populations and protect the host interior from invasion. Although excess intestinal immune activity frequently promotes inflammatory illnesses, we know little about the consequences of chronic innate immune activity exclusively in endodermal gut cells of an otherwise normal animal. To address this question, we examined the consequences of persistent inflammatory signals in adult fly intestinal progenitor cells. We found that constitutive immune activity disrupts expression of homeostatic regulators such as Notch pathway components and induces hyperplasia throughout the gut. Consistent with these observations, we found that persistent immune signals interfere with progenitor cell differentiation and exacerbate the formation of Notch-dependent intestinal tumors. These findings uncover a link between constitutive immune activity and tumorigenesis in intestinal stem cells.